ANALISIS PENERAPAN RESPONSIVE GOVERNANCE PADA APLIKASI Si D’nOK DI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KOTA SEMARANG - Rivaldo Enggal Saputra; Maesaroh Maesaroh (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2026)
This study is motivated by the persistent problems found in the implementation of digital-based public services through the Si D’nOK application at the Department of Population and Civil Registration of Semarang City, particularly regarding the responsiveness of services to public complaints and reports. This study aims to analyze the implementation of responsive governance in the Si D’nOK application and to identify the supporting and inhibiting factors affecting its implementation. The theoretical framework used in this study is the concept of responsive governance proposed by Zeithaml as cited in Rasdiana and Riski Ramadani (2021), as well as the principle of responsiveness within the good governance framework. This research employs a descriptive qualitative method, with data collected through interviews, observation, and documentation. The results show that the implementation of responsive governance in the Si D’nOK application has generally been carried out, but it has not yet been fully optimal. Several indicators indicating this suboptimal implementation include the ability to respond to citizens, service speed, timeliness of service delivery, and responsiveness to complaints, which result in delayed responses by officers, technical problems within the application system, and the absence of an integrated and systematic complaint- handling mechanism. Meanwhile, the indicators that have been implemented optimally are service accuracy and appropriateness. Supporting factors for the implementation of responsive governance include policy support, the availability of digital platforms, and organizational commitment to improving public services, which are reflected in digital technology and system integration, accessibility and public participation, and service suitability. Conversely, the inhibiting factors consist of limited human resource capacity, technical system constraints, and weak internal coordination in handling complaints, as reflected in human resource capacity limitations and the contextual intelligence of the government.